INTEGRATING THE NORTH-EAST CAUCASUS: RUSSIFICATION POLICIES IN THE LATE IMPERIAL ERA (LATE 19TH – EARLY 20TH CENTURIES) - Halidova, Ol'ga Borisovna (History, Archeology and Ethnography of the Caucasus, 2024)
The historical incorporation of diverse multinational and multi-confessional territories, inhabited by peoples at varying levels of social and cultural development, has predetermined the focus of state national policy on ensuring the unity and integrity of the country. The complex relationship between the center and the periphery compelled the government to seek the most effective ways to integrate the newly acquired territories into the Russian state system. Building on this, the paper considers the problematic issue of introducing integrative practices in the North-East Caucasus after the conclusion of the Caucasian War, within the context of the “Russification” policy. This policy served as the ideological foundation for the imperial project. In this respect, the study examines specific issues regarding the implementation of the Russification policy in the region. These issues include, on the one hand, missionary practices, and on the other hand, the introduction of the Russian language as the national language, serving as a central tool for consolidating the empire. The research draws upon the extensive domestic and international historical scholarship on Russian imperial policies towards various regions. Recognizing the abundance of existing research, this study highlights the urgency for fresh perspectives and answers within the academic community. It seeks to contribute through broad generalizations and conceptual conclusions regarding the management practices of the Russian Empire. The study concludes that while integrative practices based on the Russification brought about development in various spheres of life in the North-East Caucasus, the region’s population also developed its own strategies for adapting to imperial reforms and changes. This process allowed them to preserve their unique cultural heritage, deeply rooted in the region’s history.
Keywords: Russia; North-East Caucasus; Dagestan; empire; policy; integration; periphery; russification; education; Russian language